Factors contributing students’ creativity - Ayoufu, W.; Afshari, M.; Ghavifekr, S. (2012)
The purpose of this study was to determine the factors which could foster and enhance students’ creativity in three research universities in Malaysia. The data collected from 520 postgraduate students. Correlation analysis was employed to analyze data. Findings of this study indicated that three factors such as intrinsic motivation, psychological empowerment, and support for innovation contribute significantly to the development of students’ creativity. It is suggested that universities should create a supportive environment, assist students’ psychological empowerment and develop an innovative culture in order to enhance students’ creative thinking.